METFORMIN AND THE GUT MICROBIOTA: CHANGES AND CLINICAL IMPLICATIONS – A LITERATURE REVIEW - Natalia Klimek; Antoni Liebert; Hanna Wilska; Adam Niedziela; Dominik Domoń; Martyna Kaplińska; Dominika Domanowska (International Journal of Innovative Technologies in Social Science, 2025)
Background: Metformin remains the first-line pharmacotherapy for type 2 diabetes mellitus (T2DM), traditionally understood to act through hepatic glucose suppression and improved insulin sensitivity. However, mounting evidence indicates that metformin significantly influences the gut microbiota, which may underlie some of its metabolic and gastrointestinal effects Aim: This review explores metformin’s mechanisms of action via gut microbial modulation, its clinical effects, and side-effect implications, drawing upon recent primary and review literature. Methods: We performed comprehensive searches in databases including PubMed and Google Scholar,using terms such as metformin, mechanisms of metformin, gut microbiota, side effects of metformin, metformin mechanisms gut, and related combinations. We included studies published up to mid-2025, prioritizing human clinical trials, systematic reviews, and mechanistic animal studies. Results: Compelling evidence shows that metformin alters gut microbial composition—increasing taxa like Akkermansia muciniphila, Escherichia, and SCFA-producers—while reducing others. These shifts are linked to improved barrier integrity, altered bile acid signaling (e.g., FXR inhibition, GLP-1 increase), enhanced SCFA production, modulated metabolite profiles (e.g., BCAA, aromatic amino acids), and altered host glucose flux. Clinically, these microbiome changes likely contribute to metformin’s glucose-lowering, weight-modulating, and anti-inflammatory effects but may also underpin gastrointestinal side effects. Conclusion: The gut microbiota is a significant mediator of both beneficial and adverse effects of metformin. Ongoing and future research—especially RCTs and mechanistic human studies—will be critical for harnessing this interaction therapeutically.